Rare Cause of Dyspnea in a 34-Year-Old Patient: Multimodality Evaluation of an Aortopulmonary Window. (August 2019) - Gannon, Michael P.; Kureshi, Faraz; Burklow, Thomas R.; Benton, Charles; Sirajuddin, Arlene; Arai, Andrew E.
Abstract : Supplemental Digital Content is available in the text.